2019
DOI: 10.1590/s0004-2803.201900000-07
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Dietetic Evaluation of People With Ileostomies

Abstract: BACKGROUND: The maintenance of nutrition for the person with ileostomy is a major challenge despite to the proper management of stoma eliminations. OBJECTIVE: This study aimed to evaluate the nutritional status of people with ileostomy. METHOD: This is a cross-sectional study carried out on a population of 17 people with ileostomy enrolled in the Service of Attention to the Health of the Person with Stoma of level II, referring to a health region in Minas Gerais. The anthropometric evaluation consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…Moraes et al [ 12 ] showed weight loss in more than half of patients after ileostomy who in the majority were above 50 years old, female, married and of incomplete elementary school. A relevant study conducted by Kim et al [ 21 ] showed severe weight loss and BMI reduction, post-operatively among 72.7% ( n = 50) of patients who underwent a colostomy or prophylactic ileostomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moraes et al [ 12 ] showed weight loss in more than half of patients after ileostomy who in the majority were above 50 years old, female, married and of incomplete elementary school. A relevant study conducted by Kim et al [ 21 ] showed severe weight loss and BMI reduction, post-operatively among 72.7% ( n = 50) of patients who underwent a colostomy or prophylactic ileostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Early HOS (within 3 weeks of stoma formation) occurred in 75 (16%) of ileostomies/jejunostomies [ 23 ]. However, in less than two years after surgery, patients present adequate BMI [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The word ostomy has a Greek origin (stóma) and is a temporary or definitive opening connecting the bowels to the external environment. Intestinal ostomies are performed for the clinical control of pathological conditions that interfere with normal intestinal transit, such as neoplasms, trauma, congenital abnormalities, inflammatory diseases, and obstructions (1,2) . There are two types of intestinal ostomies (ileostomy and colostomy), which respectively consist of an anastomosis of the ileal or colic segment to the anterior abdominal wall (1) .…”
Section: Introductionmentioning
confidence: 99%